Imunorregulação na pré-eclâmpsia: estudo de mediadores inflamatórios e pró-resolutivos. - Luiza Oliveira Perucci (2016)
Preeclampsia (PE) is a disease characterized by excessive maternal inflammatory response. Annexin A1 (AnxA1) and lipoxin A4 (LXA4) are anti-inflammatory and proresolving molecules, while C reactive protein (CRP) and soluble tumor necrosis factor alpha receptor 1(sTNF-R1) are pro-inflammatory markers. Brain-derived neurotrophic factor (BDNF) is also thought to modulate inflammation. Although the proinflammatory mechanisms have been extensively studied in the last decades, the pro-resolving mechanisms are poorly understood in PE. The study of pro-resolving molecules in PE is important to better understand its etiopathogenesis and to propose new pharmacological treatments for this disease, which delivery and complete removal of the placenta is the only effective treatment. The main objective of this study was to investigate the circulating levels of AnxA1, LXA4, CRP e BDNF in PE. This study included 133 women, as follows: 41 non-pregnant, 39 normotensive pregnant and 53 PE. AnxA1, LXA4 and BDNF plasma levels were measured by ELISA, and CRP levels by immunoturbidimetric assay. The relative quantification of AnxA1 mRNA expression in peripheral mononuclear cells (PBMCs) was performed using real time PCR. Correlation analyzes among the circulating levels of these molecules, sTNF-R1 (evaluated in a previous study), the clinical characteristics and the laboratory parameters of the participants were also investigated. AnxA1, LXA4 and CRP levels were higher in PE women when compared with non-pregnant women. PE women had higher levels of AnxA1 and LXA4, decreased levels of BDNF and similar levels of CRP when compared with normotensive pregnant women. CRP levels were higher in normotensive pregnant women than in non-pregnant women, but there was no difference regarding AnxA1 and LXA4 levels. Moreover, AnxA1 mRNA levels in PBMCs were similar in the three groups. Positive correlations were detected between AnxA1 and sTNF-R1, LXA4 and CRP, LXA4 and systolic blood pressure, LXA4 and diastolic blood pressure, BDNF and diastolic blood pressure, LXA4 and white blood cell count, BDNF and pre-pregnancy body mass index; and negative between BDNF and AnxA1. In conclusion, AnxA1 and LXA4 increased plasma levels coincide with a pro-inflammatory phenotype in PE women, suggesting possible failures in counter-regulatory mechanisms of the inflammatory response. BDNF decreased levels may also contribute to the inadequate regulation of inflammation in the disease.